Low energy-consumed process of integrated anammox and in-situ fermentation-based denitrification for ultra-efficient nitrogen removal from mainstream domestic sewage. (1st February 2023) - Gong, Xiaofei; Zhang, Liang; Li, Xiyao; Zhang, Qiong; Shang, Taotao; Guo, Jingwen; Wang, Chuanxin; Wang, Shuying; Peng, Yongzhen
Abstract: Anammox is a promising biotechnology for nitrogen removal and gaining popularity in mainstream wastewater treatment. The efficient and low energy-consumed elimination of the intrinsic byproduct nitrate in anammox-mediated process is still a tough barrier and urgently demands resolving. To explore a newly green alternative for advanced nitrogen removal from domestic sewage, this study proposed a novel Integrated Anammox, Fermentation and Denitrification (IAFD) process. After 215-day operation, total inorganic nitrogen (TIN) removal efficiency markedly increased from 72.6% to 94.1% and effluent TIN dropped from 7.9 mg L −1 to 1.8 mg L −1 with influent TIN of 56 mg L −1 . Through in-situ activated sludge fermentation, 37.341 mg COD·L −1 ·d −1 organics was yielded, causing a COD/NO3 − -N of 8.9, Soluble protein (63.8%), polysaccharide (10.6%) and acetic acid (13.9%) were primary components. Candidatus_Brocadia (0.8%) and Candidatus_Competibacter (4.6%) were dominant functional bacteria, which contributed 81.1% and 18.9% to nitrogen elimination, respectively. Robust anammox (3.37 mg N·g VSS −1 ·h −1 ), fermentation-assisted denitrification and denitritation synergistically boosted N removal. The novel process required no external carbon, reduced 59.5% aeration and 35.8% external sludge. The novel process showed significantly environmental and economical advantages of low operation expenses and energy cost with no external carbon requirement, 59.5% aeration and 35.8% external sludge reduction. This work provided an energy-neutral and sustainable scheme for the advanced nitrogen removal of municipal wastewater and sludge disposal in WWTPs. Graphical abstract: Image 1 Highlights: A novel IAFD process was put to address problem of high nitrate in PN/A effluents. High N removal efficiency (94.1%) was achieved with ultra-low effluent (1.8 mg/L). WAS fermentation products (PN, PS, acetic acid) effectively assisted NO3 − removal. NO2 − produced by denitritation aided byproduct NH4 + in-situ removal via anammox. Synergy of robust anammox and denitrification boosted ultra-efficient quality.